An Analysis of the Forfeiture Regime under the Anti-Money Laundering Law - A. Rahman, Aspalella (Emerald Group Publishing Limited, 2022)
Abstract: Purpose- This paper analyzes the forfeiture regime under the Malaysian anti-money laundering law. Apart from discussing the relevant provisions, several court cases also was examined to identify the problems which arise in the implementation of such a powerful forfeiture regime. Design/methodology/approach- This paper mainly relies on statutes, laws and regulations as its primary sources of information. It is supported by several court cases and secondary data to justify the analysis. This paper also utilized analytical descriptive approach to analyze relevant forfeiture provisions from statutes and to examine current court cases regarding the implementation of the forfeiture regime. Findings – The AMLATFPUAA provides comprehensive procedures for the forfeiture of criminal proceeds. Any limitations of the previous statutory legislations have been addressed and more importantly, the AMLATFPUAA introduces more powerful and innovative measures that can facilitate the recovery of illegal proceeds from money laundering and any other serious crimes. The AMLATFPUAA also provides avenue for the bona fide third parties to contest the forfeiture order. However, it appears that such right is not easy to be materialized. Originality/value- This paper provides an analysis of the forfeiture regime under Malaysian anti-money laundering law. It is hoped that the content of this paper can provide some insight into this particular area for practitioners, academics, policy makers and legal advisers, not only in Malaysia but also elsewhere. The findings of this paper also exposes any weakness or lacunae in the aspects of application or implementation of the forfeiture regime. Thus, an integrated and effective legal solution especially on the issue of forfeiture of criminal assets could be bought forth for further accomplishment